Review of morphology, development, and evolution of the notarium in birds. Issue 9 (21st December 2021) - Aires, Alex S.; Reichert, Leici M.; Müller, Rodrigo T.; Andrade, Marco B.
Abstract: The notarium is a rigid bony structure, which resulted from the fusion of thoracic vertebrae of some pterosaurs and birds. It is high variable, ranging from two to six fused thoracic vertebrae. In this study, we reviewed and analyzed approximately 270 specimens of neornithine birds (representing 80% of the living orders) and some fossils in order to identify the number of fused vertebrae, degree and sites of vertebral fusion, occurrence of sutures, and other structures of potential phylogenetic and functional significance. These data were analyzed using a recent time‐calibrated molecular phylogenetic tree and principal component analyses analysis evaluating the relationship with long bones in order to reconstruct macroevolutionary trends related to the evolution of the notarium. The occurrence of this structure shows a mosaic distribution over neornithine phylogeny, originating several times independently, especially during the Paleogene, in predominantly ground‐dwelling forms. The notarium of these groups is characterized by: neural spines fused into single structure, intervertebral openings small to absent, large ventral keels forming ventral plates, and fused transverse processes. Derived neornithines, such as aquatic forms and long‐legged birds, have a tendency to display a decreased degree of fusion between the vertebrae, which may indicate a reduction or disappearance of the notarium.